Radical theology: an essay on faith and theology in the twenty-first century - Dalferth, Ingolf U. (Fortress Press, 2016)
Ingolf U. Dalferth develops a "radical theology" that unfolds the orienting strength of faith for human life from the event of God's presence to every present. In a concise and clear manner, Dalferth outlines the theological and philosophical approaches to hermeneutics in the modern era, in order to promote a convincing and defensible theology for the twenty-first century, critically carrying on Martin Heidegger and Rudolf Bultmann, without forgetting Karl Barth. The result of his reconstruction is a "radical theology" that neither glorifies premodern theology in an antimodern attitude nor seeks a mystical deepening of the secular, but argues for a radical change in theological perspective of the possible. In doing so, theology unfolds "limit concepts" that restrict the claims of science and philosophy critically, and develops "ideas of orientation" that illumine the ways in which human life is understood and lived in radically new ways in faith. From here, Dalferth unfolds the reality of revelation and the Christian sense of an unconditional hope that fundamentally transcends all beliefs based on mundane realities and orients the world on something beyond its own temporal horizon--its loving Creator. (Publisher)